Ludzie z pustego obszaru . People from an Empty Zone - Karabasz, Kazimierz; Ślesicki, Władysław (Poland, 1957)
"Czarna Seria" is the part of NInA Publishing's series "Polish School of Documentary Movies". Edited by Tadeusz Sobolewski, the series is devoted to different Polish documentary filmmakers and contains selected documentaries from their artistic output. The series includes films made by recognized film directors as well as by some of the forgotten masters and débutante directors.